Pore water geochemistry of sediment cores from Young Sound, NE Greenland - Wiedmann, Ingrid; Lund Paulsen, Maria; Holding, Johnna M; Winding, Mie Hylstofte Sichlau; Roy, Hans; Sejr, Mikael K; Laufer-Meiser, Katja (In: Wiedmann, I et al. (2025): Impact of Different Types of Meltwater Runoff on Pelagic and Benthic Processes in Young Sound, NE Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986456, 2025)
This dataset contains measurements of porewater geochemistry in sediment cores from Young Sound. The samples for the measurements were taken in August 2019 with a Kajak-corer and the pore water was extracted by centrifugtation.
Keywords: Fjord; fjord pelagic biochemistry; fjord sediment biogeochemistry; Glacier; iron; Organic carbon; oxygen microprofiles; sulfate reduction rates